Hybrids of thienopyrimidinones and thiouracils as anti-tubercular agents: SAR and docking studies - Pisal, Mahesh M.; Nawale, Laxman U.; Patil, Manoj; Bhansali, Sujit G.; Gajbhiye, Jayant M.; Sarkar, Dhiman; Chavan, Subhash P.; Borate, Hanumant B. (European Journal of Medicinal Chemistry, 2017)
A number of hybrid molecules containing thienopyrimidinones and thiouracil moieties were designed, synthesized and tested against Mycobacterium tuberculosis H37Ra wherein it was observed that the compounds 11-1514 exhibited antitubercular activity in vitro (MIC 7.6–19.1 μg/ml, 12–35 μM) against dormant stage while compound 15 exhibited antitubercular activity in vitro against dormant (MIC 23.4 μg/ml, 41 μM) as well as active (MIC 25.4 μg/ml, 45 μM) stage. Structural modifications of compound 15 were carried out to study the structure-activity relationship and it was observed that compound 18 exhibited antitubercular activity comparable to compound 15. Cytotoxicity studies revealed that these molecules were non-toxic. The docking study of compound 15 showed that there was binding with the active site of mycobacterial pantothenate synthetase. Further docking studies led to the synthesis of the compounds 16 and 17 and the antitubercular activity screening results showed that these compounds have significant antitubercular activity. The compounds 15-18 (MIC 11–29 μg/ml, 19–51 μM) can be used as starting points for further optimization. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures and the present results will be very useful in the development of a new class of antimycobacterial agents.

H5IO6, as an efficient reagent for the aromatization of tetrahydro-β-carbolines: total synthesis of norharman, harmane, harmine, kumujian-C, and orthoscuticellines B - Sabane, Jagjivan K.; Gaikwad, Sunil V.; Gajbhiye, Jayant M.; Kumar, Pradeep (ChemistrySelect, 2026)
A new method is reported for the synthesis of beta-carbolines and their derivatives using H5IO6 in DMSO solvent. The method is mild and efficient for oxidative decarboxylation and aromatization of tetrahydro beta-carbolines (TH beta C), resulting in good to excellent yields (70% to 88%) of beta-carbolines. This protocol has further been utilized for the synthesis of beta-carbolines based natural products, for examples, norharmane, harmane, harmine, Kumujian-C, and Orthoscuticellines A and B.
Keywords: aromatization; beta-carboline; H5IO6; Harmine; orthoscuticellines; Oxidative